Talent management impact towards employee retention / Nur Azma Abdullah - Abdullah, Nur Azma (Faculty of Business and Management, 2018)
This study is to investigate the relationship between Talent Management and Employee Retention. Three objectives have been determined in order to achieve the purpose of this study. First is to identify the relationship between compensation and employee retention. Second objective is to identify the relationship between job security and employee retention and lastly, the relationship between career advancement and employee retention. The population of this study consists of 185 employees from departments in Yayasan Selangor, while the sample consists of 185 respondents. The data were collected by distribute 185 questionnaires and 141 returned questionnaires were used in the study. The questionnaires designed based on three independent variables that are expected to affect employee retention which are compensation, job security and career advancement. To analyses the data, descriptive, correlation, and regression analyses was used. Hence, the results from this study reveal that there is a positive and significant relationship between compensation and employee retention. However, there are no positive and significant relationship between job security and career advancement between employee retention. In addition, there are many others factors that may influence employee performance which are not included in this research. The sample of this study only limited to the employee that are working in departments in Yayasan Selangor.